Torus palatinus. Report of two cases - María Lorena Re Domínguez; Rosalba Riveros; Tatiana Moreno; Beatriz María Di Martino Ortiz; Mirtha Rodríguez Masi; Oilda Knopfelmacher; Lourdes Bolla de Lezcano (Our Dermatology Online, 2016)
The torus is a non-neoplastic slow growing bone protuberance, which is usually manifested before the age of 30; Set in the hard palate is called "Torus Palatinus", and located in the lower jaw - "Torus mandibularis". In most cases, the diagnosis is usually incidental, during clinical examination, due to other reasons. The reason is that they are usually asymptomatic and patients are not aware of carrying a torus; hence the conservation treatment, unless it poses problems for the patient. We report two cases of incidental detected palatal torus in women.